Identification of Toxigenic Fungi And its Respective Toxins in Dark Raisins Commercialized in Votuporanga- SP (Revista Brasileira Multidisciplinar, 2015)
Mycotoxins are secondary metabolites produced by some filamentous fungi that have toxic properties. The main way of exposure to that toxin is usually through the ingestion of contaminated food even if it is in small quantity but continuously it can induce to its accumulation in the body and cause an intoxication, affecting many organs and systems, especially the liver, kidneys and the nervous system. The most detected mycotoxins are produced by fungi from the genus Apergillus, Penicillium and Fusarium. The raisins are products obtained from the partial loss of water from the ripe fruit by drying, presenting high content of sugar and low activity of water, fact that favors the growth of fungi, principally A. niger and A. carbonarius which produce resistant spores to processing. This study aimed to achieve the isolation and identification of fungi which produce the mycotoxin and its respective toxins in dark raisins in bulk and packaged in the commercial establishment itself using microculture methods and thin layer chromatography. Thepresence of A. niger and Penicillium spp were detected, the first ones being producers of ocratoxina and A. flavus, the producer of aflatoxina. Therefore the research showed the contamination by toxigenic fungi in the collected samples in 82% of the evaluated establishments.
Keywords: Dried Fruit; Intoxication; Mycotoxins.